Variáveis Fenométricas e Rendimento de Grãos do Crambe Associado a Níveis de Compactação de um Latossolo Argiloso - Dias, Patrícia Pereira (2014)
The crambe because it is a culture that can be part of a sustainable system is presented as an alternative for the production of renewable energy from its potential to produce oil for biodiesel chain. This study aimed to evaluate the growth of crambe under different soil densities as well as their behavior when subjected to water stress after flowering. The experiment was conducted in a heated vegetation of the Universidade Estadual do Paraná, campus Cascavel - Paraná - Brasil. The treatments were formed by the factorial 6x2 (six soil densities - 0.9, 0.99, 1.08, 1.17, 1.26 and 1.35 Mg m-3 and two blades - continuous irrigation and limited irrigation at flowering). The experimental design was completely randomized. The fenometric variables were evaluated: plant height, stem diameter, fresh weight of plant, plant dry mass, grain yield, number of leaves, root depth, root volume and root dry mass. Soil density between 1.08 Mg m-3 and 1.17 Mg m-3, the root of crambe goes deeper when water restriction. For the other variables there was a decrease in quality when subjected to higher densities of soil and water restriction.